The influence of corporate governance on firm performance: an analysis of listed commercial banks in China - Zhang, Zhujia (2022)
This paper aims to examine the impact of corporate governance on the performance of commercial banks in China. In terms of corporate governance mechanisms, this paper mainly considers internal corporate governance, which is measured by five indicators: ownership concentration, board size, proportion of independent directors, the number of annual shareholder meetings and CEO compensation. ROA, Tobin's Q, Non-Performing Loan ratio and ROE are used to evaluate bank performance. In this study, 16 Chinese listed banks were selected from 2010 to 2021, including 5 state-owned banks and 11 joint-equity banks. In processing these data, fixed effects regression analysis is used to explore the influence of corporate governance on bank performance, and random forest regression analysis (see appendix) is conducted to compare whether the results are consistent. In addition, a robustness test was conducted using data from 2010-2019 and a DID (difference in difference) model was built to test the findings considering the pandemic factor. The results of the fixed effects regression model show that corporate governance mechanisms are connected to bank performance in China, even though not all corporate governance variables are significantly associated with bank performance. In general, the findings suggest that larger boards are likely to provide much more value to banks, whereas a higher level of ownership concentration may result in a decline in a bank's profitability. Meanwhile, the influence of corporate governance on bank performance may not be significantly affected by COVID-19. By analyzing the banking industry in a developing economy (China) that is subject to relatively considerable government interference, this study fills a gap in the body of existing literature. In response to this study, four implications are made to assist boards in improving the corporate governance framework of their bank performance.